Quality of life and wellbeing among breast cancer patients in Lahore, Pakistan - Ayub, Fiza; Khan, Tahir Mehmood; Baig, Mirza Rafi; Amin, Muhammad Usman; Tahir, Humera (Frontiers in Oncology, 2023)
Breast cancer has a high incidence rate, emphasizing the necessity of enhanced information of health-related quality of life (HRQOL) in this population of patients. The aim of this study was to identify the factors influencing the QOL and the patients are suffering in Pakistan. A cross-sectional study was conducted on females with breast cancer, and three instruments were used: FACT-B Version 4 questionnaire, WHO causality assessment scale, Naranjo’s algorithm and a demographic/clinical characteristics section, and given to a random sample of 130 Pakistani women. Data analysis included descriptive analysis, independent sample t-test and ANOVA test. The patients’ mean age was 49.10 (SD=10.89); 98.5% were married 98.5 %. The mean score for physical well-being was 18.34(SD 5.92; IQR 11), for social/family well-being was 16.33(SD 6.3; IQR 11.25), for emotional well-being was 13.6 (SD 3.55; IQR 6), for functional well-being was 17.13 (SD 3.73; IQR 6) and for breast cancer subscale was 24.86 (SD 3.64; IQR 4). The study found that the age, entitlement, recurrence, marital status, salary, number of doses, duration of cancer treatment and chemotherapy sessions were significantly related to QOL terms in the assessment of FACT-B scale. The WHO causality evaluation scale determined that 78.1 percent of the responses were "probable" and 20.1 percent were "possible." According to the Naranjo’s algorithm assessment scale, 80 percent of ADRs were “probable”, whereas 18.4 percent were declared “possible”. Chemotherapy Induced Anemia was the most often reported ADR in 64.6% of patients, followed by Chemotherapy Induced Nausea and Vomiting (61.5%). Health care practitioners must acknowledge and take into account the significance of QOL in addition to therapy for breast cancer patients in order to enhance their health. The findings of this study will aid in filling gaps in current unknown knowledge and identifying sites where patients require additional assistance. Because cancer and chemotherapy clearly have a negative impact on individuals' QOL, Oncologists must concentrate on strategies that help cancer patients during their sickness and treatment while also enhancing self-care and QOL. Those with cancer will benefit from emotional well-being and adaptation to their disease.